Răspuns :
[tex]x^{2} + \frac{3x}{3} = {x}^{2} + \frac{4x}{4} \\ 12 {x}^{2} +12x = 12 {x}^{2} + 12x. \div 12 \\ {x}^{2} + x = {x}^{2} + x \\ {x}^{2} - {x}^{2} = x - x \\ 0 = 0[/tex]
Adevarat
Deci oricare ar fi X exista ca solutie a ecuației
Adevarat
Deci oricare ar fi X exista ca solutie a ecuației
X^2+3x/3=x^2+4x/4
x² + x = x² + x
x² - x² + x - x = 0
0 = 0 (A)
[tex]oricare\,ar\;fi\;x\,\in\,{R}\;este\;solutie\;pentru\;ecuatia\;data\,![/tex]
x² + x = x² + x
x² - x² + x - x = 0
0 = 0 (A)
[tex]oricare\,ar\;fi\;x\,\in\,{R}\;este\;solutie\;pentru\;ecuatia\;data\,![/tex]